2014
DOI: 10.3111/13696998.2014.914033
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous vs intravenous rituximab in patients with non-Hodgkin lymphoma: a time and motion study in the United Kingdom

Abstract: SC rituximab was associated with reduced active HCP time and costs vs IV rituximab, as well as reduced patient time in the treatment room. Switching from IV to SC rituximab could increase treatment room capacity and patient throughput, as well as improving the patient experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 5 publications
1
64
0
Order By: Relevance
“…It simplifies the treatment experience for both patients and health-care professionals, reduces the burden on health-care resources and is likely to improve patient quality of life and treatment adherence. 8,21,26,27 One multinational study demonstrated SABRINA trial: NCT01200758…”
Section: Clinical Practice Considerations Benefits For Service Providersmentioning
confidence: 99%
See 1 more Smart Citation
“…It simplifies the treatment experience for both patients and health-care professionals, reduces the burden on health-care resources and is likely to improve patient quality of life and treatment adherence. 8,21,26,27 One multinational study demonstrated SABRINA trial: NCT01200758…”
Section: Clinical Practice Considerations Benefits For Service Providersmentioning
confidence: 99%
“…Patient throughput, waiting list times and hospital efficiency were greatly improved. 26,27 Nurses' experiences to date support the use of the SC formulation of rituximab in routine clinical practice. In a published survey of 65 nurses who had administered SC rituximab to a total of 166 patients at various investigational sites, 72% reported the SC rituximab delivery process as 'easy' or 'very easy'; 95% rated the experience as 'positive' or 'very positive' and 95% of nurses indicated they would recommend SC administration to patients.…”
Section: Stagementioning
confidence: 99%
“…Studies have demonstrated that patients receiving IV rituximab in addition to chemotherapy not only experience improved progression-free survival, but also superior overall survival [5][6][7] . The preparation and administration of IV rituximab is resource-intensive, requiring 2-6 hours to calculate the appropriate dose based on body surface area (bsa), to prepare fluids, and to titrate and administer the infusion 4,[8][9][10] -all of which occur in addition to the preparation and administration time associated with chemotherapy treatment, which is administered sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…After one initial IV administration of rituximab is tolerated, sc rituximab administered as a fixed dose provides an alternative to the IV formulation in dlbcl and fl, as currently used in rituximab-containing regimens. The sc administration of rituximab takes significantly less time than IV administration 9,13 ; however, to monitor for side effects, administration must still occur in a systemic therapy suite 11 . Nevertheless, sc rituximab simplifies administration and reduces the treatment burden both for patients and for already constrained health care resources, including systemic therapy suite time.…”
Section: Introductionmentioning
confidence: 99%
“…In our data, the apparent rate of reactions was higher for those subcutaneous doses where premedication was given than for those given without; although this may be explained by increased patient surveillance as the ‘covered’ doses were given in the context of clinical trials. It has already been shown that subcutaneous administration of Rituximab improves cost effectiveness and patient experience when compared with the intravenous route (Rule et al , ). Administering subcutaneous Rituximab without pre‐medication further reduces administration time, improving efficiency and patient experience; and means that patients are not exposed to the potential sedative effects of antihistamines.…”
mentioning
confidence: 99%